2013
DOI: 10.1007/s10899-013-9394-5
|View full text |Cite
|
Sign up to set email alerts
|

On Being Attracted to the Possibility of a Win: Reward Sensitivity (via Gambling Motives) Undermines Treatment Seeking Among Pathological Gamblers

Abstract: Unfortunately, only a small percent of pathological gamblers seek the professional help they need. In the current study, we test the idea that individual differences in reward sensitivity should predict whether a pathological gambler has sought treatment—the odds of treatment seeking should decrease as reward sensitivity increases. This hypothesis rests on the proposition that reward sensitive pathological gamblers should find treatment seeking aversive because doing so would remove a route to reward. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Being that a key component of our CBT intervention involves cutting ties with people and/or environments that could potentially cause a patient to relapse, patients who possess stronger social bonds to gambling might be more reluctant to stay in treatment when confronted. This rationale is consistent with other research that found that higher reward sensitivity levels undermined treatment seeking among pathological gamblers (Sztainert et al., 2014) and as such, patients with this trait could very well be less motivated to stay in treatment. Other studies propose that the GD in early stages could be categorized as an ego-syntonic disorder because the patient seeks immediate reward and does not experience associated distress (El-Guebaly, Mudry, Zohar, Tavares, & Potenza, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Being that a key component of our CBT intervention involves cutting ties with people and/or environments that could potentially cause a patient to relapse, patients who possess stronger social bonds to gambling might be more reluctant to stay in treatment when confronted. This rationale is consistent with other research that found that higher reward sensitivity levels undermined treatment seeking among pathological gamblers (Sztainert et al., 2014) and as such, patients with this trait could very well be less motivated to stay in treatment. Other studies propose that the GD in early stages could be categorized as an ego-syntonic disorder because the patient seeks immediate reward and does not experience associated distress (El-Guebaly, Mudry, Zohar, Tavares, & Potenza, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, research has found that individuals with high reward sensitivity are motivated to engage in behaviors that provide both internal and external reinforcement in the form of enhancement/winning motives and social motives, respectively (Sztainert, Wohl, McManus, & Stead, 2014; Wardell et al., 2015). Similarly, greater CB tendencies have been positively associated with reward sensitivity, which has been reported to be a powerful predictor of CB severity (Lawrence, Ciorciari, & Kyrios, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have supported this contention. Sztainert, Wohl, McManus, and Stead (2014) found, in a sample of pathological gamblers, that reward sensitivity (i.e., a personality trait representing a tendency to seek out positive reinforcement) predicted both enhancement and social gambling motives, but did not predict coping motives. Using a 30-day experience sampling design, Goldstein, Stewart, Hoaken, and Flett (2014), in a sample of at-risk gamblers, determined that negative affectivity was positively correlated with coping motives, positive affectivity was positively related to enhancement motives, and impulsivity was positively related to both coping and enhancement motives.…”
Section: Personality and Gambling Motivesmentioning
confidence: 85%
“…This relationship might be clarified by examining more fine-grained facets of extraversion. For instance, MacLaren et al (2011a) ascertained that the positive emotions facet of extraversion is associated with fewer gambling problems, while Sztainert et al (2014) found that reward sensitivity was associated with heightened enhancement motives and gambling problems. Future research might explore these relationships longitudinally to isolate the components of extraverted personality associated with specific patterns of gambling motives.…”
Section: Extraversionmentioning
confidence: 99%
“…Persistence in the face of loss and continued engagement in chance-based tasks despite adverse consequences is the defining behaviour exhibited by problem gamblers. In terms of clinical applications, the current research suggests that beliefs in luck is a factor endorsed by many, not just those with disordered gambling (Wohl, Young, & Hart, 2007), and therefore, might be an area of focus for prevention initiatives aimed to promote responsible play (Wohl et al, in press) and treatment seeking (Sztainert, Wohl, McManus, & Stead, 2013).…”
Section: Managerial Implicationsmentioning
confidence: 97%